An alternative educational method: Computer-based simulation program for advanced cardiac life support education - Öktem, Begüm; Kılıçaslan, İsa; Keleş, Ayfer; Bildik, Fikret; Demircan, Ahmet (Journal of Surgery and Medicine, 2021)
Background/Aim: Technology is gaining importance in medical education, along with distance learning and technology-enhanced learning systems. In certain conditions, such as the Covid-19 outbreak, adapting technology to our medical education is essential. Computer-based simulation is one of those technologies that can be used in medical education. We aimed to measure the contribution of computer-based simulation to students’ knowledge of cardiac rhythms in the advanced cardiac life support (ACLS) curriculum, compared to the classic educational method. Methods: Interns (6th-grade medical students) were included in this observational study and divided into a study group and a control group. Both groups received a 2.5-hour-long ACLS rhythms lecture. Afterward, case studies were completed with a computer-based simulation program in the study group and with the classical didactic method in the control group. The participants took a multiple-choice test to measure the level of knowledge before (pre-test) and 4 weeks after (post-test) the training. “ACLS Simulator 2016” licensed program was used. Results: A total number of 80 medical students were included in the study. There were 35 (43.75%) males and 45 (56.25%) females, with a mean age of 23.7 (1.1) years. The mean number of correct answers in the pre-training test was 12.6 (3.2), and similar between the two groups (P=0.131), but significantly increased to 15.7 (3.3) (P<0.001) after the training. In the post-training test, the study and the control groups answered 16.0 (3.6) and 15.5 (3.1) questions correctly, respectively (P=0.477). Conclusion: Adapting a computer-based simulation program improves students’ level of knowledge. Case scenario training with a computer-based simulation is as effective as the classical method.